ANALYSIS OF THE INCIDENCE OF BRAIN TUMORS IN UKRAINE AND THE SUMY REGION IN 2017–2021 - Gyryavenko, Nataliia; Kolesnyk, Volodymyr (Eastern Ukrainian Medical Journal, 2024)
Background. Tumours of the brain and other parts of the central nervous system, despite the relatively low incidence, cause significant mortality in all age groups. In addition, these tumours are characterized by great histological diversity, which complicates diagnosis.Aim. Analysis of statistical indicators of the incidence of brain tumours in the population of Ukraine and the Sumy region in 2017–2021.Materials and methods. Based on data from the National Cancer Registry of Ukraine, an analysis of the incidence of malignant brain neoplasms in the population of Ukraine and the Sumy region in 2017–2021 was carried out. The histological archives of the Department of Pathology of the Sumy Regional Clinical Hospital and the Department of Pathology of the Sumy State University were also analyzed.Results. The average incidence of malignant brain neoplasms was 3.5 ± 0.28 cases per 100,000 population of the Sumy region, which was lower than the national level (3.96 ± 0.09 cases per 100,000 population of Ukraine). The average mortality rate for 2017–2021 was 2.3 ± 0.19 deaths per 100,000 population of Sumy Region, which was also lower than the national level (2.58 ± 0.07 deaths per 100,000 population of Ukraine). Morbidity and mortality prevailed among men. Among children, the average incidence rate in 2017–2021 was 2.12 ± 0.11 cases per 100,000 child population of Ukraine, and the average mortality rate was 0.8 ± 0.05 cases per 100,000 child population of Ukraine. During this period, 25 patients were operated on in the Sumy region, of which six men (24%) and 19 women (76%) had the primary diagnosis of meningioma. The average age of the patients was 64.88 ± 2.11 years, and among the histological variants of meningiomas, the following were recorded: 13 meningothelial (52%), eight psammomatous (32%), three mixed meningothelial-psammomatous (12%) and one fibrous meningioma (4%).Conclusions. Morbidity and mortality due to malignant brain neoplasms in the Sumy region in 2017–2021 were slightly lower than the national indicators, but this may indicate insufficient diagnosis. Among non-malignant tumours, 25 cases of meningiomas were recorded, most of which were characteristic of women aged 65.